Acute Effects of Cyclic Limb Compressions on mRNA Expression of Angiogenic Factors in Skeletal Muscle - Roseguini, Bruno T.; Soylu, Mehmet; Whyte, Jeffrey; Yang, Hsiao T.; Newcomer, Sean C.; Terjung, Ronald L.; Laughlin, M. H. (Lippincott Williams & Wilkins, 2010)
…
57th Annual Meeting of the American-College-Sports-Medicine/Inaugural World Congress on Exercise is Medicine -- JUN 05, 2010 -- Baltimore, MD